Acute intestinal obstruction due to ascariasis in a child: A case report. (March 2023) - Sulmiati,; Nurmantu, Farid; Ahmadwirawan,; Mariana, Nita; Habar, Tommy Rubiyanto; Faruk, Muhammad
Abstract: Introduction and importance: Ascariasis is one of the most common parasitic infections worldwide, especially in tropical and subtropical developing countries with poor personal hygiene and sanitation. This condition is a staggering worldwide public health problem with high morbidity and mortality. Intestinal obstruction is an acute presentation that occurs in cases where clumps of worms form, causing partial or complete obstruction of the intestinal lumen. Case presentation: We report a case of a 5-year-old boy with total intestinal obstruction due to Ascaris lumbricoides, who underwent exploratory laparotomy and enterotomy to remove the worm masses. Clinical discussion: Infestation with roundworms is widespread in developing countries. While the majority of the intestinal obstruction they cause may be treated conservatively, in some circumstances, surgery may be required. Conclusion: Infestation with roundworms is widespread in developing countries, and although the majority of the intestinal obstruction they cause may be treated conservatively, in some circumstances, surgery may be required. Highlights: Infestation with roundworms is widespread in developing countries. Most intestinal obstruction due to ascariasis may be treated conservatively. In some circumstances, surgery may be required. Hygiene, anthelmintic medication, and education are critical for prevention.